(untitled) (Clinics, 2019)
OBJECTIVES: This study sought to determine prevalences of injuries associated with CrossFits training and assess profiles of these injuries and the affected athletes. METHODS: Data were collected over a 12-month period using a questionnaire administered directly to practitioners at CrossFits-affiliated fitness centers in the state of Sa˜o Paulo, Brazil. Of the 414 participants, 157 (37.9%) participants reported having suffered an injury while practicing CrossFits. RESULTS: The injury rate was 3.24 injuries per 1,000 hours of training. The probability of injury for athletes who had practiced CrossFits for longer than 12 months was 82.2%, which was higher than the corresponding probability for beginner athletes. The probability of injury was 5-fold higher among competitive-level athletes than that among less-experienced athletes. No evidence of an association between the occurrence of injuries during CrossFits practice and any of the following athlete characteristics was found: age, gender, practice of other sports, weight, and height. The incidence of injuries in this sports modality was similar to that in other modalities, including Olympic weight lifting (OWL), basic weight lifting, and artistic gymnastics. CONCLUSION: CrossFits appears to be a training program that is suitable for different age groups when performed in a safe environment and with assistance from qualified professionals.